2020
DOI: 10.1111/1471-0528.16242
|View full text |Cite
|
Sign up to set email alerts
|

Hysteropexy in the treatment of uterine prolapse stage 2 or higher: laparoscopic sacrohysteropexy versus sacrospinous hysteropexy—a multicentre randomised controlled trial (LAVA trial)

Abstract: Objective To investigate whether laparoscopic sacrohysteropexy (LSH) is non‐inferior to vaginal sacrospinous hysteropexy (SSHP) in the surgical treatment of uterine prolapse. Design Multicentre randomised controlled, non‐blinded non‐inferiority trial. Setting Five non‐university teaching hospitals in the Netherlands, one university hospital in Belgium. Population 126 women with uterine prolapse stage 2 or higher undergoing surgery without previous pelvic floor surgery. Methods Randomisation in a 1:1 ratio to L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 42 publications
2
33
1
Order By: Relevance
“…Fifteen studies including 4,120 cases (2,409 cases for SSLF, 1,439 cases for ASC, and 272 cases for LSC) fulfilled the inclusion criteria and were included in the final analysis (Fig. 1) [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. All publications were full-text articles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifteen studies including 4,120 cases (2,409 cases for SSLF, 1,439 cases for ASC, and 272 cases for LSC) fulfilled the inclusion criteria and were included in the final analysis (Fig. 1) [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. All publications were full-text articles.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the studies included are shown in Table 1. There were 5 RCTs [14,20,21,25,28] (level of evidence: 2b) [29]; 8 retrospective studies [15,16,18,19,22,24,26,27] and 2 prospective studies (level of evidence: 2b-3b) [17,23]. As for surgical procedures, 10 studies compared SSLF with ASC [15,16,18,[20][21][22][23][24][25]28] [14,17,19,26], and 1 compared ASC, LSC, and SSLF [27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the LAVA trial [23], laparoscopic sacrohysteropexy was found to be non-inferior for surgical failure compared with sacrospinous hysteropexy. The 5-year follow-up of the original SAVE-U study by Schulten et al [24] showed that treatment of uterine prolapse with sacrospinous hysteropexy is effective and has lower risk of recurrent bothersome uterine prolapse or retreatment of the apical compartment compared with vaginal hysterectomy with uterosacral ligament suspension.…”
Section: Discussionmentioning
confidence: 97%
“…We thank Huang et al for their interest and for taking the time to raise some questions regarding our study 1,2 …”
mentioning
confidence: 99%